(untitled) (Al-Academy, 2025)
Sustainability was considered one of the contemporary concepts as a major revolution in the seventies of the twentieth century. Most researchers considered it a concept synonymous with the strategy and sustainability of time and the financial investment of science in a way that helps in the development of societies. It is a multi-level and multi-branch concept that was circulated within the global development sectors, as it was framed by technology, politics, economics and the environment, until Sustainability has become the culture of our time. According to these data, the researcher adopted the concept of sustainability within a societal culture that interacts with heritage and communication in contemporary formation within a research structure consisting of an introduction in which the research problem was presented, founded by the following question: How is the culture of sustainability represented in contemporary Iraqi formation? A study in the continuity of heritage. The importance of the research came as it is a topic that discusses the culture of sustainability in its relationship with the contemporary Iraqi formation. The goal was set by identifying the culture of sustainability in the contemporary global formation. A study of heritage continuity within objective, spatial and temporal boundaries ( 2000-2024 AD ) The introduction was completed by defining the concepts ( culture, sustainability, heritage, and communication ), while the theoretical body came from four sections: the first, the cognitive concept of the culture of sustainability, and the second, the cognitive concept of the concepts of heritage and communication. The third topic represented applications in developing sustainability in art, and the fourth topic represented culture. Sustainability, heritage, and communication in contemporary Iraqi formation. From this, the researcher obtained a number of results. 1- Iraqi plastic arts kept pace with most scientific techniques with multiple approaches such as optimally employing contemporary techniques through scientific techniques. 2- Sustainability has formed a societal culture that the artist has supported through his artistic achievement, establishing an aesthetic and guiding discourse for society. 3- Employing materials in a sustainable artwork is considered creativity, especially if its structure carries the heritage system as an authentic communicative data. The artist was able to reconcile heritage as an existential cultural system and the possibility of preserving it through art, framing his achievement with a communicative value through which authenticity was effectively achieved, so that the culture of sustainability became a joint in the aesthetic construction of the Iraqi artist